Investigating the Size Effect on the Compressive Strength of Self- Consolidating Concrete Containing Taftan Pumice and Micro-Silica - Seyed Roohollah Mousavi (Iranian Society of Structrual Engineering (ISSE), 2021)
Self-compacting concrete is a special concrete that flows with its weight in the form and does not need to shake. based on experimental findings, its compressive strength decreases with an increase in the specimen size; this phenomenon is called “size effect and its beginning is a nonlinear failure in concrete and other fragile materials. The purpose of this study was to investigate the size effect on compressive strength of cubic and cylindrical specimens in self-compacting concrete containing pozzolanic materials of microsilica and Taftan Pumice. To this end, the least squares (LSM) method and Bezant’s Size effect rule have been used to analyze the data. Seven designs consist of 3 different mixing designs of 2.5, 5 and 10% cement weight replaced by micro silica also 3 mixing designs containing 15, 20 and 25% weight of cement replaced by Pumice. An additional design was also made as a reference mix design. All Mix designs were cast in various size-cubic molds and also in standard cylindrical molds. According to the results, Mixes with 5% micro-silicon (M5) and 20% Pumice (P20) showed the highest compressive strength. The compressive strength ratio of cubic to cylindrical specimens was studied in all mixing designs. The results of the experiments show that self-compacting concrete cube specimens have a higher compressive strength than standard cylindrical specimens, and the compressive strength ratio of cubic specimens to standard cylindrical specimens with increasing cubic sizes from 5 to 15 centimeters decrease. On the other hand, the results show that the effect of size has decreased in designs with 5% microsilica and 15% pumice.